Genetic influences on nicotinic α5 receptor (CHRNA5) CpG methylation and mRNA expression in brain and adipose tissue. (December 2015) - Ramsay, Jessica; Rhodes, C.; Thirtamara-Rajamani, Keerthi; Smith, Ryan
Abstract Introduction The nicotinic α5 receptor subunit, encoded byCHRNA5, harbors multiple functional single nucleotide polymorphisms (SNPs) that affect mRNA expression and alter the encoded protein. These polymorphisms are most notably associated with drug-taking behaviors and cognition. We previously identified common SNPs in a distant regulatory element (DRE) that increaseCHRNA5 mRNA expression in the human prefrontal cortex (PFC) and confer risk for nicotine dependence. Genome-wide epigenetic studies in PFC and adipose tissue find strong effects of the DRE SNPs on CpG methylation. However, it is unclear whether DRE SNPs influence CpG methylationen route to modulatingCHRNA5 mRNA expression. It is also unclear whether these polymorphisms affect expression in other brain regions, especially those mediating drug-taking behaviors. Results By measuring total and allelicCHRNA5 mRNA expression in human habenula and putamen autopsy tissues, we found thatCHRNA5 DRE variants considerably increase mRNA expression by up to 3.5-fold in both brain regions. Our epigenetic analysis finds no association between CpG methylation andCHRNA5 mRNA expression in the PFC or adipose tissues. Conclusions These finding suggests the mechanisms responsible for the genetic modulation of CpG methylation and mRNA expression are independent despite the DRE SNPs being highly associated with both measures. Our findings support a strong association between the DRE SNPs and mRNA expression or CpG methylation in the brain and periphery, but the independence of the two measures leads us to conclude that environmental factors affecting CpG methylation do not appear to directly modulate gene expression.